A pre-coital pill? A preliminary in vitro study. Issue 3 (1st July 2000) - Kovacs, Gabor T; Hendricks, Jacqui; Summerbell, Deborah; Baker, H W Gordon
Abstract : The use of the progestogen-only pill as a 'pre-coital contraceptive' was tested by in vitro studies of sperm-mucus interaction. The results suggest that a single tablet of levonorgestrel 30 μg, or norethisterone 350 μg, was effective in preventing sperm migration in the cervical mucus about 12 hours later. This suggests that the progestogen-only pill may be effective as a 'morning before pill'.